Technological innovation attached to sustainable stimulation: an analysis in the Technological Center of Porto Digital in Pernambuco – Brazil (Research, Society and Development, 2021)
The study aims to understand how the Technological Center of Porto Digital in the city of Recife contributes to the sustainable, economic and social development in Pernambuco, considering the sustainable initiatives stimulated among the companies linked to the Center. To identify the projects developed, as well as the results obtained by the actions, bibliographic researches and documental analyses were carried out, coming from academic publications, public agencies' productions, reports and information disclosed on Porto Digital's website. These actions made it possible to observe the sustainable practices that are encouraged or carried out and identified benefits as to the preservation of the environment, the expansion of the economy and the quality of life in society. Considering that the initiatives generated by Porto Digital are still scattered in the literature and that this factor hinders the analysis by interested parties, entrepreneurs, students and researchers, the analysis presented aims to contribute to the bibliographic field, emphasizing technological innovation and sustainable development.